การพัฒนาแบบสอบวินิจฉัยมโนทัศน์เรื่องพันธะไอออนิกโดยใช้โมเดลวินิจฉัยพุทธิปัญญาจีไดนาสำหรับนักเรียนมัธยมศึกษาปีที่ 4 - วรุตม์ ผิวงาม (จุฬาลงกรณ์มหาวิทยาลัย, 2020)
The purposes of this research were to 1) explore misconceptions about ionic bonding, 2) develop the ionic bonding diagnostic test with feedback, and 3) examine the quality of the ionic bonding diagnostic test with feedback. The research was divided into 3 phases. In phase 1, the misconceptions about ionic bonding were explored. Phase 2 was carried out to develop the ionic bonding diagnostic test with feedback, and the ionic bonding diagnostic test with feedback was validated in phase 3. The target group was 1,234 tenth grade students. Two instruments that were developed in this research included a checklist and an ionic bonding diagnostic test. Q-matrix was validated through IOC and PVAF indices. Item discrimination, TPR, TNR, PCA and PCV indices were analyzed to assess validity and accuracy of PVAF index, and the KR20 was used to quantify test reliability. The research findings were as follows: 1. 30 out of 37 misconceptions about ionic bonding were found in the target group of students and they were classified into 3 skills: 1) explaining the formation of ionic bonding, 2) writing and naming ionic compounds, and 3) identifying interactions between ionic compounds. 2. The ionic bonding diagnostic test consists of thirty-multiple-choice items, each of which was scored 1 or 0 for correct and incorrect responses, respectively. The distractors were developed based on students’ misconceptions about ionic bonding. 3. The ionic bonding concept diagnostic test had discrimination indices ranging from 0.062 to 0.773. There were 20 items with discrimination indices above the criteria, representing 66.7% of all items. The PVAF index was able to specify the students skills correctly for 18 items, representing 60.0% of all items. As for the results of TPR and TNR indices, the test did not meet the criteria. However, PCA and PCV showed that the Q-matrix had a classification accuracy of 99.21%, suggesting that the Q-matrix could specify students’ skills accurately. The test had a reliability coefficient of 0.845 which was acceptable high and passed the criteria. The feedback obtained from the analysis of strengths and areas for improvement for individual students were reported to teachers of the target group of students as useful feedback information for correcting students’ misconceptions about ionic bonding.